Is a Multi-Slider Interface Layout Responsible for a Stimulus Spacing Bias in the MUSHRA Test? - ZIELIŃSKI, Sławomir (Archives of Acoustics, 2015)
The multi-stimulus test with hidden reference and anchors (MUSHRA) is commonly used for subjective quality assessment of audio systems. Despite its wide acceptance in scientific and industrial sectors, the method is not free from bias. One possible source of bias in the MUSHRA method may be attributed to a graphical design of its user interface. This paper examines the hypothesis that replacement of the standard multi-slider layout with a single-slider version could reduce a stimulus spacing bias observed in the MUSHRA test. Contrary to the expectation, the aforementioned modification did not reduce the bias. This outcome formally supports the validity of using multiple sliders in the MUSHRA graphical interface.